2013
DOI: 10.1182/blood-2012-12-471300
|View full text |Cite
|
Sign up to set email alerts
|

Tribbles in acute leukemia

Abstract: There is growing research interest in the mammalian Tribbles (Trib) family of serine/threonine pseudokinases and their oncogenic association with acute leukemias. This review is to understand the role of Trib genes in hematopoietic malignancies and their potential as targets for novel therapeutic strategies in acute myeloid leukemia and acute lymphoblastic leukemia. We discuss the role of Tribs as central signaling mediators in different subtypes of acute leukemia and propose that inhibition of dysregulated Tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
50
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 42 publications
(52 reference statements)
1
50
0
Order By: Relevance
“…6,8,9 In line with these observations, MYC and TRIB1 have been shown to co-operate in AML. 6,8,9 The oncogenic role of TRIB1 in AML relies at least in part on the ability of TRIB1 to regulate the stability of the transcription factor C/EBPα via the E3 ligase COP-1.…”
supporting
confidence: 55%
See 3 more Smart Citations
“…6,8,9 In line with these observations, MYC and TRIB1 have been shown to co-operate in AML. 6,8,9 The oncogenic role of TRIB1 in AML relies at least in part on the ability of TRIB1 to regulate the stability of the transcription factor C/EBPα via the E3 ligase COP-1.…”
supporting
confidence: 55%
“…6,7 TRIB1 and TRIB2 but not TRIB3 seem to play a relevant role in leukemia. 6,8,9 Thus, TRIB1 (which was initially identified as a gene placed at a retroviral integration site 10 ) has been shown to be over-expressed in patients with acute myeloid leukemia (AML). 6,8,9 Moreover, the human TRIB1 gene is located in the same chromosome region as MYC, a gene that is also frequently amplified in AML.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, a TRIB1 singlenucleotide polymorphism was found associated with nonalcoholic fatty liver disease in humans while the same investigators showed that TRIB1 expression affects hepatic lipogenesis and glycogenesis through multiple molecular interactions (including a molecular interaction with MLXIPL or CHREBP, a hepatic lipogenic master regulator) (Ishizuka et al 2014). In addition to a role in lipid metabolism, there is a substantial literature on the role of tribbles in cancer (Liang et al 2013).…”
Section: Tribbles Homologmentioning
confidence: 99%